Targeting caspase-8/c-FLIPL heterodimer in complex II promotes DL-mediated cell death - Hillert-Richter, Laura K.; König, Corinna; Ivanisenko, Nikita V.; Reinhold, Dirk; Lavrik, Inna N. (Frontiers in Cell and Developmental Biology, 2024)
Death receptor (DR) networks are controlled by the assembly of the Death-Inducing Signaling Complex (DISC) and complex II. The family of small molecules FLIPins (FLIP interactors) were developed to target the caspase-8/c-FLIPL heterodimer. FLIPin compounds were shown to promote apoptosis and caspase-8 activation at the DISC upon stimulation with death ligands (DLs) such as CD95L and TRAIL. To further investigate the role of FLIPin compounds in the DL-mediated cell death response, we analyzed their effects in combination with DLs and SMAC mimetics treatment. FLIPins were found to enhance cell viability loss and cell death induced by DL and SMAC mimetics in acute myeloid leukemia (AML), colon and pancreatic cancer cells. FLIPins enhanced both DL/BV6-induced apoptosis and DL/BV6/zVAD-fmk-induced necroptosis via an increase in complex II formation. Our results indicate that targeting the caspase-8/c-FLIPL heterodimer plays a prominent role in enhancing cell death induced by co-stimulation of DL/SMAC mimetics and opens new therapeutic strategies for targeting DR networks.